The Design, Synthesis, and Characterization of Resveratrol Derivatives Modified by Different γ-Aminobutyric Acid Esters - Bing Ren Tian; Jia Yue Liu; Hu Rong Ge; Zhi Zhong Wang; Shao Yun Huang; Yu Ying Wang; Qing Huang; Rui Xia Zhang (Journal of Chemistry)
A novel series of resveratrol modified by γ-aminobutyric acid esters were designed and synthesized. Then, the products were characterized by 1H-NMR, 13C-NMR, and MS, and the melting point was determined. Molecular water solubility, polar surface area, and octanol-water partition were calculated, which correlated well with molecular transport through membranes and, therefore, enabled prediction of transport properties of drugs.